Modular passivity-based modelling of piezoelectric actuators - Ignacio Díaz; Héctor Ramírez; Yann Le Gorrec; Yongxin Wu (Mathematical and Computer Modelling of Dynamical Systems, 2025)
This paper is concerned with the constructive, modular and easy to implement passivity-based rate-dependent modelling of piezoelectric actuators (PZAs) using the port Hamiltonian (PH) framework. The proposed model incorporates hysterons to capture the hysteresic behaviour of PZAs, resulting in a causal bond-graph representation and a simplified explicit PH formulation. The proposed model is an input-affine port-Hamiltonian system that is shown to be asymptotically stable with respect to an arbitrary equilibrium configuration. The model is experimentally validated over a large range of operation frequencies using a commercial piezoelectric actuator and compared to a Bouc-Wen model of the same order.